Remote intelligent perception system for multi-object detection - Alazeb, Abdulwahab; Chughtai, Bisma Riaz; Al Mudawi, Naif; AlQahtani, Yahya; Alonazi, Mohammed; Aljuaid, Hanan; Jalal, Ahmad; Liu, Hui (Frontiers in Neurorobotics, 2024)
During the last few years, a heightened interest has been shown in classifying scene images depicting diverse robotic environments. The surge in interest can be attributed to significant improvements in visual sensor technology, which has enhanced image analysis capabilities. Advances in vision technology are having a major impact in the areas of multiple object detection and scene understanding. These tasks are an integral part of a variety of technologies, including integrating scenes in augmented reality, facilitating robot navigation, enabling autonomous driving systems, and improving applications in tourist information. Despite significant strides in visual interpretation, numerous challenges persist, notably encompassing semantic understanding, occlusion, orientation, insufficient availability of labelled data, uneven illumination including shadows and lighting, variation in direction, and object size and changing background. To overcome these challenges, we proposed an innovative scene recognition framework, which proved to be highly effective and yielded remarkable results. Firstly, we perform preprocessing using kernel convolution on scene data. Secondly, we perform semantic segmentation using UNet segmentation. Then, extract features from these segmented data using DWT Discrete wavelet transform, Sobel and Laplacian, textual (local binary pattern analysis). To recognize the object, we have used deep belief network and then find the object-to-object relation. Finally, AlexNet is used to assign the relevant labels to the scene based on recognized objects in the image. The proposed system's performance was validated using three standard datasets: PASCALVOC-12, Cityscapes, and Caltech 101. The accuracy attained on the PASCALVOC-12 dataset exceeds 96%, while achieving a rate of 95.90% on the Cityscapes dataset. Furthermore, the model demonstrates a commendable accuracy of 92.2% on the Caltech 101 dataset. This model showcases noteworthy advancements beyond the capabilities of current models.